Pendekatan Kontekstual Dalam Meningkatkan Pemahaman Konsep Aqidah di MAN Kelas X MAN Model Banda Aceh - Miskul Makhtum (Universitas Islam Negeri Ar-Raniry Banda Aceh, Aceh, Indonesia., 2019)
The background of this study was more specifically related to the contextual approach: linking science with daily life, which could help improve students’ understanding on aqidah/creed materials, their ability to think, and their learning experiences. Thus, the students could implement them in real life. The study conducted in Class X of MAN Model Banda Aceh, aimed at investigating the implementation of the contextual approach, the application of the contextual approach which could increase the understanding of the Aqidah concept, and the understanding of Aqidah concept of the students taught using the contextual approach and the conventional approach. The research employed quantitative descriptive with quasi experimental method. Data were collected by essay pretest and essay post test, teachers’ and students’ observation, and documentation. The research findings showed that the implementation of the contextual approach on aqidah learning covered the scope of Aqidah Islam and sub-materials such as the definitions, and the principles of aqidah. The learning method of aqidah included using seven components of the contextual approach: constructivism, inquiry, modeling, frequently asked questions, group learning, modeling, and real judgment. The teaching and learning activities were carried out through discussions in accordance with the lesson plans. Further, the observation analysis of the teachers’ ability level (TKG) showed that the descriptive statistics of the teaching activity was 4.51≤TKG t1-α or 15.38> 1.6923, making Ho rejected and Ha accepted. It can be meant that the students’ posttest was better that the pretest. Moreover, the learning outcomes of the aqidah learning of the students of Class X IPA 2 and Class X IPA 5 reflected that those taught with the contextual outperformed those with the conventional learning, as shown here based on the significance level α = 0.05 and degree of freedom (df) = 66. The ttable obtained was t_(0,975)(66) = 1.997 so that tcount < ttable (0.59 µ2 was accepted.